2011
DOI: 10.1111/j.1440-1797.2011.01509.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of SBR759, a novel calcium‐free, iron(III)‐based phosphate binder, in Asian patients undergoing hemodialysis: A 12‐week, randomized, open‐label, dose‐titration study versus sevelamer hydrochloride

Abstract: SBR759 showed superior phosphate control with a favorable tolerability profile compared to sevelamer-HCl in hemodialysis patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
29
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 18 publications
(34 reference statements)
1
29
0
Order By: Relevance
“…Participants and investigators were blinded in three studies 17,18,22 and outcome assessors were blinded in four studies. 15,17,18,22 The number of participants lost to follow-up ranged from 13.1 to 38.1% but did not differ between the treatment and control groups. Only three studies 15,18,22 were analyzed on an intention-to-treat basis.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Participants and investigators were blinded in three studies 17,18,22 and outcome assessors were blinded in four studies. 15,17,18,22 The number of participants lost to follow-up ranged from 13.1 to 38.1% but did not differ between the treatment and control groups. Only three studies 15,18,22 were analyzed on an intention-to-treat basis.…”
Section: Resultsmentioning
confidence: 99%
“…The remaining 18 full-text articles were reviewed for more detailed assessment, and 10 studies were excluded because of duplicate reports. Finally, 8 studies [15][16][17][18][19][20][21][22] with 2018 participants met our inclusion criteria and were included in our meta-analysis. The selection process for studies included in the systematic review is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations